2022
DOI: 10.3390/nu14030414
|View full text |Cite
|
Sign up to set email alerts
|

Could I-FABP Be an Early Marker of Celiac Disease in Children with Type 1 Diabetes? Retrospective Study from the Tertiary Reference Centre

Abstract: Patients with type 1 diabetes (T1D) are at higher risk of celiac disease (CD). Recently, intestinal fatty acid binding protein (I-FABP) has been shown to be a serological biomarker of impaired intestinal barrier in CD. Thus, the aim of this study was to verify whether I-FABP could be an early marker of CD in pediatric T1D patients. I-FABP was measured in sera of patients with T1D (n = 156), active CD (n = 38), T1D with active CD (T1D-CD, n= 51), and age-matched healthy children (n = 55). Additionally, I-FABP w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Significantly elevated I-FABP levels in T1D patients, independent of disease duration, confirm our previous reports on epithelial damage in pediatric T1D and the utility of I-FABP as a serological marker of intestinal barrier dysfunction [ 24 ]. It is noteworthy that those substances whose concentration was not affected by the duration of the disease (IAPP, proIAPP, and I-FABP) are markers described as taking part in the pathomechanism of T1D.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Significantly elevated I-FABP levels in T1D patients, independent of disease duration, confirm our previous reports on epithelial damage in pediatric T1D and the utility of I-FABP as a serological marker of intestinal barrier dysfunction [ 24 ]. It is noteworthy that those substances whose concentration was not affected by the duration of the disease (IAPP, proIAPP, and I-FABP) are markers described as taking part in the pathomechanism of T1D.…”
Section: Discussionsupporting
confidence: 88%
“…In a number of studies, selected biologically active substances were indicated as contributing to the etiology (IAPP [ 16 , 31 , 32 , 33 , 34 , 35 , 36 ], proIAPP [ 17 , 18 , 37 ], I-FABP [ 24 ]), course (CST [ 38 , 39 ], ChgA [ 40 , 41 , 42 ]) or the development of various complications (neuropathy—NGF [ 43 , 44 , 45 ], cardiovascular complications—PAF [ 26 , 46 , 47 ], and cardiovascular complications and nephropatia—UMOD [ 28 , 48 , 49 ]). In the current study, we assessed the diagnostic usefulness of these indicators present in T1D patients’ sera and confirmed statistically significant differences between their concentrations in the group of children with T1D and healthy children, but only some of them (NGF, ChgA, CST and PAF) were affected by disease duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid increase in paracellular permeation is associated with malnutrition and absorptive disorder, which may help to explain the compromised body composition of the MetS-D group. In the clinical setting, increased intestinal permeability is reported in individuals with T1D and metabolic syndrome (28). In these patients, the presence of inflammation and disruption in the intestinal microbiota are indicated as the cause of this damage (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs are important to the maintenance of epithelial-intestinal barrier permeability, reducing the translocation of bacteria and their products from the gut to the bloodstream [47]. The reduction in the abundance of SCFA-producing bacteria in the gut microbiota is possibly involved with the breakdown of the intestinal epithelial barrier observed in diabetic patients, attested by the measure of circulating levels of lipopolysaccharide (LPS) and/or intestinal fatty acid binding protein [48,49]. Furthermore, LPS, a component of the cell wall of Gram-negative bacteria and potentially opportunistic pathogenic bacteria found in the gut microbiota of diabetic patients, enhanced intestinal permeability in vitro and in vivo [50,51].…”
Section: Diabetes the Hpa Axis And Microbiotamentioning
confidence: 99%